1995
DOI: 10.1902/jop.1995.66.12.1032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ND:YAG Laser Irradiation and Root Planing on the Root Surface: Structural and Thermal Effects

Abstract: Effects of ND:YAG laser irradiation on untreated and root planed tooth roots were investigated to determine whether a cleaning effect and/or removal of smear layer could be achieved without concomitant microstructural or thermal damage. Sixty (60) healthy extracted teeth were either untreated, irradiated only, root planed only, or irradiated and root planed. Intra-pulpal and surface temperatures were monitored during irradiation, then SEM was performed. Smear layer elimination was achieved without inducing har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 31 publications
2
44
0
2
Order By: Relevance
“…In previous clinical studies, it has been demonstrated that lasers are an effective tool in the field of root conditioning to improve the outcome of regenerative periodontal therapies by favoring the attachment of the regenerated periodontal structures. [32][33][34][35][36][37][38][39][40][41][42][43] The Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces. 37,38 The Nd:YAG laser, with noncontact delivery mode and short irradiation time, has caused no damage to or alteration of root surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous clinical studies, it has been demonstrated that lasers are an effective tool in the field of root conditioning to improve the outcome of regenerative periodontal therapies by favoring the attachment of the regenerated periodontal structures. [32][33][34][35][36][37][38][39][40][41][42][43] The Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces. 37,38 The Nd:YAG laser, with noncontact delivery mode and short irradiation time, has caused no damage to or alteration of root surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43] The Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces. 37,38 The Nd:YAG laser, with noncontact delivery mode and short irradiation time, has caused no damage to or alteration of root surfaces. 37 In addition, Tewfik et al 39 reported effects of Nd:YAG laser on root cementum topography and fibroblastic attachment, and suggested that the modification of cementum surfaces depends on the energy level of the laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This risk can exist through the penetration of short wavelengths or the conductive heat effects arising from long wavelength char that is super-heated. [5][6][7][8][9] It is advisable, therefore, to assess the thickness, vascularity and position of any target 6,[10][11][12] during the removal of a giant cell granuloma. Laser therapy has been cited as a possible modality in treating this condition.…”
Section: Laser-tissue Interaction and Keratinised Mucosa -Risk Analysismentioning
confidence: 99%